An introduction to engaged Buddhism - Fuller, Paul (Bloomsbury Academic, 2022)
"This textbook introduces and explores the ideas, practices, and philosophy of the movement of engaged Buddhism. This new movement argues that suffering is not just caused by cravings of the mind, but also by political and social factors. Therefore, engaged Buddhists 'engage' with social issues to achieve liberation. Paul Fuller outlines the movement's origins and principles. This is followed by a comprehensive analysis of the central themes and issues of engaged Buddhism, offering new insights into the formation of modern Buddhism. The range of issues covered includes politics, gender, environmentalism, identity, blasphemy and violence. These are illustrated by case studies and examples from a range of locations where Buddhism is practised. Discussion points and suggested further reading, including internet resources, are provided at the end of each chapter, which will further enrich undergraduates' grasp of the topic"--